Friends forever - Hale, Shannon; Pham, LeUyen (New York : First Second, 2021)
Shannon is in eighth grade, and life is more complicated than ever. Everything keeps changing, her classmates are starting to date each other (but nobody wants to date her!), and no matter how hard she tries, Shannon can never seem to just be happy. As she works through her insecurities and undiagnosed depression, she worries about disappointing all the people who care about her. Is something wrong with her? Can she be the person everyone expects her to be? And who does she actually want to be?
Booklist starred, July 2021
Horn Book, September 2021
School Library Journal starred, August 2021
3.0.
5-8.
HL420
Keywords: Hale, Shannon -- Comic books, strips, etc. -- Juvenile literature; Hale, Shannon -- Cartoons and comics; Female friendship -- Comic books, strips, etc -- Juvenile literature; Middle school girls -- United States -- Biography -- Comic books, strips, etc -- Juvenile literature; Depression in adolescence -- Comic books, strips, etc -- Juvenile literature; Self-acceptance -- Comic books, strips, etc -- Juvenile literature; Schools -- Comic books, strips, etc -- Juvenile literature; Female friendship -- Comic books, strips, etc; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Middle school girls -- Biography -- Cartoons and comics; Depression in adolescence -- Cartoons and comics; Schools -- Cartoons and comics; Cartoons and comics; Autobiographical comics; Nonfiction comics; Comics (Graphic works); Graphic novels; High-low nonfiction